2019
DOI: 10.1186/s40478-019-0740-4
|View full text |Cite|
|
Sign up to set email alerts
|

In vivo real-time dynamics of ATP and ROS production in axonal mitochondria show decoupling in mouse models of peripheral neuropathies

Abstract: Mitochondria are critical for the function and maintenance of myelinated axons notably through Adenosine triphosphate (ATP) production. A direct by-product of this ATP production is reactive oxygen species (ROS), which are highly deleterious for neurons. While ATP shortage and ROS levels increase are involved in several neurodegenerative diseases, it is still unclear whether the real-time dynamics of both ATP and ROS production in axonal mitochondria are altered by axonal or demyelinating neuropathies. To answ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 85 publications
5
33
0
Order By: Relevance
“…In wildtype neurons, a first burst generated a H2O2 but no ATP peak and a second burst applied 30 min later generated a second H2O2 peak followed by an ATP rise 20 min later. In neurons from R94Q mice, this ATP peak was greatly attenuated [15] which is in line with our findings that prior H2O2 exposure affects ATP production.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In wildtype neurons, a first burst generated a H2O2 but no ATP peak and a second burst applied 30 min later generated a second H2O2 peak followed by an ATP rise 20 min later. In neurons from R94Q mice, this ATP peak was greatly attenuated [15] which is in line with our findings that prior H2O2 exposure affects ATP production.…”
Section: Discussionsupporting
confidence: 92%
“…Maybe the hydrogen peroxide challenge affected succinate oxidation. Others also reported that R94Q mitochondria failed to upregulate ATP production following burst neuronal activation [15]. In wildtype neurons, a first burst generated a H2O2 but no ATP peak and a second burst applied 30 min later generated a second H2O2 peak followed by an ATP rise 20 min later.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…AAV2/9 was significantly more efficient than AAV2/rh10 regarding the transduction rate at the injection site (83% vs 32% respectively on average). This high transduction rate is clearly correlated to the injection protocol as an intrathecal injection of the same vectors of newborn or adult mice resulted in the transduction of a large amount of neurons and glial cells [4,22,23,53] but no mSC in sciatic nerves. While we cannot rule out a transduction of mSC in nerve roots close to the spinal cord after intrathecal injection, intra nerve injection appears as the most efficient way to transduce these cells in vivo.…”
Section: Discussionmentioning
confidence: 88%
“…In the case of ATeam, binding of ATP to the sensor does not produce a hydrolysis of the molecule (Imamura et al, 2009), and there is no evidence that ATeam exerts a buffering effect, a phenomenon well described for chemical ion indicators of Ca 2+ (McMahon and Jackson, 2018). ATeam and its mitochondrial variant mito-ATeam were recently employed in vivo for imaging of ATP dynamics in cortical neurons and in peripheral axons (Baeza-Lehnert et al, 2019;Van Hameren et al, 2019). In summary, these results, together with the possibility to perform calibrations as demonstrated in the present study, show that ATeam and its variants are suitable tools for the detection of intracellular ATP in sub-cellular compartments, cell cultures, and tissue slices, as well as in vivo.…”
Section: Properties Of Ateam In Astrocytes and Neuronsmentioning
confidence: 99%